Pentecostal hermeneutics : a reader - Martin, Lee Roy. (Religious Studies, Theology and Philosophy E-Books Online, Collection 2014, ISBN: 9789004262492., 2013)
In Pentecostal Hermeneutics: A Reader Lee Roy Martin brings together fourteen significant publications on biblical interpretation, along with a new introduction to Pentecostal hermeneutics and an extensive up-to-date bibliography on the topic. Organized chronologically, these essays trace the development of Pentecostal hermeneutics as an academic discipline. The concerns of modern historical criticism have often stood at odds with Pentecostalism's use of Scripture. Therefore, over the last three decades, Pentecostal scholars have attempted to identify the unique characteristics and interpretive practices of their tradition and to offer constructive proposals for a Pentecostal hermeneutic that would be critically valid and, at the same time, be consistent with the Pentecostal ethos and conducive for the continued development of the global Pentecostal movement. Contributors include: Rickie D. Moore, John Christopher Thomas, Jackie David Johns, Cheryl Bridges Johns, John W. McKay, Robert O. Baker, Scott A. Ellington, Kenneth J. Archer, Robby Waddell, Andrew Davies, Clark H. Pinnock, and Lee Roy Martin.